Analisis Kelayakan Usahatani Bunga Krisan Pada Masa Pandemi Covid-19 Kelurahan Kakaskasen Dua Kecamatan Tomohon Utara Kota Tomohon - Kaparang, Egga Claudia; Tangkere, Ellen Grace; Katiandagho, Theodora Maulina (Sam Ratulangi University, 2024)
The purpose of this study was to analyze the feasibility of chrysanthemum farming during the Covid-19 pandemic in Kakaskasen Village. This research conducted in September-October 2021 and reported in 2023. The data collected in this study are primary data obtained directly from chrysanthemum farmers through intervievs using a questionnaire. Secondary data is obtained from institutions or agencies related to research. Sampling in this study using purposive sampling method. Intentional sampling by taking the Krekeli Framer Group which has 10 farmers as member, but only 1 farmer who cultivates chrysanthemum during the Covid-19 pandemic and that farmer is the sample. The results showed that chrysanthemum farming in Kakaskasen Dua Village, North Tomohon Sub-district is profitable. This is evident based on the results of research income received by farmers in one planting season amounted to IDR 11.541.250 and the total costs incurred in one planting season is IDR 5.522.500. Thus, the R/C value of chrysanthemum flower farming is 3,04 which means that every IDR 1,00 used in one farm, will generate revenue of IDR 3,04.